STUDI PENYEBAB TERJADINYA LONGSOR PADA JALAN PROVINSI LINTAS SIPAHUTAR-PANGARIBUAN DESA SIABAL-ABAL II - Semangat Marudut Tua Debataraja; Jubel Pardede (Jurnal Darma Agung, 2020)
The problem of the level of influence of soil carrying capacity is one of the things needed to be considered in a planning and work of a civil construction. This is because the soil serves as a medium that withstands the load or action of the construction built on it. Stabilization using sand materials is one way to meet the necessary power requirements. Weather and temperature changes in the field are factors making the ground unstable. Type of stabilized soil is silt originating from jl.Pancasila Batangkuis Regency Deliserdang. This research was conducted using mixed sand with mixed variations of 25%, 40%, 55% and 65%. Then, DST testing and Index properties were done for each sample. Based on the results of this test the soil obtained classification According to AASHTO criteria that is that this land including silt land or with a general assessment as the soil very well up to very well. This is because the plasticity (PI) of the soil sample is 8.69 <10% (max 10) and the plastic limit (PL) is 19.18% <30% and (LL) 27.87% <40% so it is included in group A-2 -4. According to the criteria of USCS (1982), based on the results of the test, soil classification obtained is a type of soil sand (LL) 8.69% <50% so it includes the ML cohort. The increase of soil bearing capacity based on test results by modeling with square foundation is as follows: Original soil qu = 6.46 t / m², Sand Supplement 25% = 6,665 t / m², Sand Supplement 40% = 9,888 t / m², Sand Supplement 55 % = 12,231 t / m², Sand Supplement 65% = 12,273 t / m² and for the foundation of path shape are: Original soil qu = 5,140 t / m², Sand Supplement 25% = 5,175 t / m², Sand Supplement 40% = 7,776 t / m², Sand Supplement 55% = 9,918 t / m², Sand Additional 65% = 14,870 t / m². The more variation of the added sand mixture results in decreasing moisture content which will make the soil carrying capacity increase.